Pengaruh Jumlah Produksi, Kurs Dollar Amerika Serikat dan Luas Areal Lahan Terhadap Ekspor Karet Indonesia Tahun 1993-2013 - Dewi, A A Putri Kusuma; Suresmiathi, A A Ayu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 2, Februari 2015 (pp.71- 137), 2015)
ABSTRACT In the era of free trade as it is today, an international competition in the trade activity will be intense. For that each country trying to improve the results of its flagship export goods. One of the Indonesian export mainstay behind the decline of Indonesia's economy is export of rubber plantations which provide a source of huge foreign exchange for the nation's economy.The purpose of this study was to examine the effect of the amount of production, the United States dollar exchange rate and the areal extent of the Indonesian rubber exports in 1993-2013. This study uses secondary data sourced from the Central Bureau of Statistics and Bank Indonesia are then analyzed using multiple linear regression analysis. The results based on multiple linear regression analysis showed that the effect of the amount of production, the United States dollar exchange rate and the total area of land simultaneously significant effect on Indonesian rubber exports in 1993-2013. However partial, variable number of production are positive and significant effect. Keyword: the amount of production, the United States dollar exchange rate, the total area of land, rubber exports